Un référent musical ? La réception des mélodies de troubadours par les trouvères - Florence Mouchet (Revue des Langues Romanes)
The presumably prolific and numerous encounters between troubadours and trouvères left apparent marks in the lyrical of the latter. The reception of the troubadours’work manifested itself, at musical level, by an early assimilation of Occitan melodies, integrated to the oïl corpus through various adaptative processes (especially contrafacta and melodic quotations). Study of those musical processes, and musical pieces using them, explicitely attests the referent status given to troubadours by trouvères, and refines, in a complementary axis to the poetical one, the troubadour’s representation in the 13th century.